Variation of Cement Types Usage for Compressive Strength of Concrete Quality F'c 35 Mpa - Muhammad Humaidi; Khairil Yanuar; Aunur Rafik; Herliyani Farial Agoes; Reza Adhi Fajar; Surat (PT FORMOSA CENDEKIA GLOBAL, 2023)
Various research and experiments in the field of concrete are ocurred as an effort to improve the quality of concrete, material technology and implementation techniques obtained from the results of these studies and experiments are intended to answer the increasing demands on the use of concrete and overcome the obstacles that often occur in the implementation work at outdoor. One of them is to get high quality concrete. By using a variety of types of cement. The purpose of this study was to obtain a high quality f'c 35 MPa and to find out whether the cement type PPC (gresik) and the cement type PCC (tonasa and three wheels) where this type of cement has a high compressive strength achieves a quality of f'c 35 MPa. The test object used is cylindrical in shape and the planned quality is 35 MPa which will be tested at the age of 7 days, 14 days, 28 days and 56 days. This research was carried out in the BANJARMASIN STATE POLYTECHNIC laboratory. From the results of this study with the same mixture proportions, the characteristic compressive strength for the Gresik Cement Variation (PPC) = 28.665 MPa, the Cement Tonasa Variation (PCC) = 35.779 MPa, and the Characteristic Compressive Strength for Three Wheel Cement Variations (PCC) =31,961MPa. It can be concluded that the compressive strength of the concrete characteristics of the tonal cement variation is higher than that of the Gresik and Three Roda cement variations